MONITORING AND QUANTIFICATION OF SOIL WATER CONTENT AND FLUXES IN DEEP LAYERS OF WHEAT CULTIVATED SOILS TO IMPROVE WATER USE EFFICIENCY - Iqbal, N.; Iqbal, T.; Ishaque, W.; Rafiq, M.; Fazil, M.; Ghaffar, A. (The Nucleus, 2013)
Calculation of irrigation scheduling (IS) and improvement of irrigated water use efficiency (WUE) requires precise measurement of soil water content and fluxes in the soil layers. Deep irrigation fluxes in agricultural field of wheat crop at the Nuclear Institute of Agriculture & Biology (NIAB), Faisalabad, Pakistan were monitored and quantified using radio and stable isotope techniques. The time variant soil moisture content data were also used to determine the fluxes by water balance technique. The fluxes determined by isotope and water balance technique were compared and found in good agreement. On the basis of the flux data, suggestions were made to improve the irrigation plan in accordance with crop water consumption and to reduce the water loss through deep percolation.